Biodiesel and biolubricant production from different vegetable oils through transesterification. Issue 12 (25th May 2020) - Encinar, José María; Nogales, Sergio; González, Juan Félix
Abstract: A study about the production and characterization of biodiesel and, especially, biolubricants from different raw materials (ie, rapeseed, a mixture of corn and sunflower, and frying oils) is here performed. Optimal chemical conditions were used to carry out the transesterification of biodiesel and biolubricants, hence obtaining high yields in all investigated cases. The physical properties, such as fatty acid methyl ester profile, viscosity, viscosity index and oxidative stability, among others, are analyzed. The biodiesel products comply with the standards, according to the characteristics covered in this research. Regarding the biolubricants, the viscosity values are analogous to those found in the literature but showing longer induction points. These properties appear to be highly influenced by the fatty acid profile of the raw material, which is an important factor for both biodiesel and biolubricant performance. Therefore, the initial characterization of vegetable oils is an important stage for the optimal design of biorefineries. Finally, the use of transesterification for biodiesel and biolubricant production is also justified, as many valuable products (eg, glycerol, fatty acid methyl esters, and fatty acid complex esters) are obtained and some by‐products (eg, methanol) can be reused. Abstract : The use of different oils to produce biolubricants is here studied. The properties of different vegetable oil compositions are investigated. This study highlights the importance of the initial characterization of vegetable oils for the optimal design of biorefineries